Malignant potential and associated risk factors of oral lichen planus - Reis, Dennise de Araujo; Oliveira, Beatriz Simas de; Silva Neto, José Inácio da; Cunha, Lizandra Oliveira; Lins, Marina Souza de Oliveira; Gonzalez, Thaís Feitosa Leitão de Oliveira (Journal of Oral Diagnosis, 2021)
Introduction: Oral Lichen Planus (OLP) is a chronic, immune-mediated inflammatory disease of uncertain pathogenesis, which affects about 0.5-2% of the world population, being more frequent in middle-aged women. The clinical presentations are reticular, erosive, atrophic, bullous, papular, and plaque-like forms. Its malignant potential, and its risk factors, are topics of clinical importance, although controversial. Aim: To perform a literature review about the malignant potential of OLP and the main risk factors involved. Material and Method: The Scielo and Pubmed databases were used for search the articles, using the combinations “oral lichen planus AND malignancy” and “oral lichen planus AND malignant neoplasm” were selected 19 articles published in English and Spanish, over the last ten years, in addition to classic papers. Results and Discussion: Studies report that the malignant potential of OLP is low (around 1.12%), although it is still uncertain, due to the lack of consistent diagnostic criteria. However, there is a suggestion that the malignant potential occurs when OLP shows as the erosive form or when it is on the tongue. An association between tobacco and alcohol consumption and the Hepatitis C virus is a topic that still needs to be clarified. Also, studies suggest that the release of inflammatory cytokines from chronic inflammation may contribute to this process. Final Considerations: Although questionable, the potential for malignant transformation of OLP, as well as its risk factors, should be further studied. Therefore, it is necessary to standardize the diagnostic criteria and documentation. Also, more longitudinal studies are essential to elucidate the role of different carcinogens in the pathogenesis and malignant potential of OLP.